Potensi Anak Yatim Berbasis Pendidikan Kemandirian Perspektif Al-Qur’an (Studi Penelitian di Yayasan Yatim Al-Mubarok Kota Tangerang) - Soejono, Sri Rosmalina; Saihu, Made; Anwar, Hamdani (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2023)
This article explains the exploration of the potential of orphans through independent education to create communicative, collaborative, creative and constructive learning, which is based on the values of the Koran. The approach used in this paper is a psychological and spiritual constructive educational approach; an approach that can optimize independence in orphans and is relevant to the Al-Qur'an. The conclusion of this research explains that first; Al-Mubarok Orphanage components maximize the potential of orphans through psychological and spiritual assistance. Second; The al-Mubarok Orphanage component has systematic stages in an effort to explore the potential of orphans. Third; The learning process at al-Mubarok Orphanage is carried out using the learning by doing technique. Fourth; optimizing the independence of orphans is carried out through involvement in entrepreneurial activities. Fifth; Orphans at the al-Mubarok Orphanage are often involved in various social and religious events, giving them a positive impact both psychologically and spiritually. This conclusion is an attempt to develop the argument of Jean Peaget's constructivist educational approach, which assumes that a person can learn independently by looking at the people around him.